Developing Spanish oral Skills Through Argumentative Activities Focused on the Arhuaco Culture - Duque Briceño, Jessica Juliette; Malagón Viasus, Juan Carlos; Vásquez, Diana Marcela; Castellanos Jaimes , Judith (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article describes the implementation of argumentative activities focused on the Arhuaco Culture, and its effect on senior highschooler’s oral skills. We carried out a qualitative study and implemented one action research cycle: the action phase consisted of a pedagogical intervention of 3 applications (4 class periods each one). During the observation phase, we collected data, and for the reflection phase, we analyzed such data. Triangulation and data reduction allowed us to identify patterns and propose two categories of analysis as initial findings. We concluded that students knew few argumentative methods, but by dealing with topics in an interactive way or topics that were interesting to students, they told many arguments to defend their ideas. The intercultural lessons focused on the Arhuaco culture improved students' argumentative skills since they could be contextualized to back up some of their ideas. The intervention also allowed the students to see Colombia as a multicultural country